GNSS interference reduction method for CORS site planning - Reza Septiawan; Agung Syetiawan; Arief Rufiyanto; Nashrullah Taufik; Budi Sulistya; Erik Madyo Putro (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Precision, Navigation, and Timing (PNT) system based on Global Navigation Satellite System (GNSS) becomes significant in the air, land, and sea traffic management. Integrity of GNSS is significant to provide a reliable real time PNT system such as CORS (Continuously Operating Reference Stations). GNSS Interference due to intentional or unintentional surrounding signal source may decrease the integrity of GNSS signal. Monitoring and identification of potential GNSS interference sources in the surrounding environment of CORS is significant. This paper proposed a methodology to reduce potential GNSS interference in a planned CORS site by first simulating the radiation pattern of potential source of interference to GNSS signal in the planned CORS sites. Thereafter ambient noise levels in the location of CORS may be measured to provide a reference point for analyzing the other potential sources of interferences. Based on these results, optimal location of CORS is chosen with the lowest possible unintentional interference signal from their surrounding. Measurement has been conducted in the location of CORS owned by BIG (Indonesian Agency for Geospatial Information), which is located in the rooftop of a building neara telecommunication tower.This method is necessary for CORS site planning to reduce potential GNSS interference sources in the environment of alternative sites.